(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Possibilities of introduction in the educational program of fine on departments of pedagogical educational establishments of computer technologies for rationalization and increase to the coefficient of mastering of useful information, forming of the developed creative personality of student are examined in the article.